1960
DOI: 10.21236/ad0491094
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Lobar Buckling of Cylindrical Shells Under External Hydrostatic Pressure

Abstract: A solution to Gerard's differential equations for plastic buckling of cylindrical shells is found for the case of lobar buckling under hydrostatic pressure. An approximate formula based on this solution is then obtained for buckling in the inelastic region.According to this formula, the buckling pressure is a function of the cylinder geometry and the secant and tangent mnoduli as determined from a stress-strain intensity diagrain for the shell material. Agreement with experiments on ring-stiffened cylinders is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1965
1965
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…By substituting this result into (5), it is found that Equation (9) is similar in form to equations (16) and (17) of reference [3], but the constants are different. This result is a very good approximation to equation (5) provided that 6 > 2.…”
Section: >mentioning
confidence: 98%
See 1 more Smart Citation
“…By substituting this result into (5), it is found that Equation (9) is similar in form to equations (16) and (17) of reference [3], but the constants are different. This result is a very good approximation to equation (5) provided that 6 > 2.…”
Section: >mentioning
confidence: 98%
“…An equation equivalent to (5) has been given previously in [3], If the prebuckling end restraint is neglected, Nv = pa; i.e., = 1. Then equation (5) becomes…”
Section: Elastic Shell Buckling Between Stiffenersmentioning
confidence: 99%
“…The buckled shape is taken to be constant along the axis of the cylinder, and thus no longitudinal buckling modes resulting from axial forces are considered. Although some solutions for longitudinal buckling are available (Almroth, 1962;Reynolds, 1962;Weingarten, 1962), to be consistent with the fact that analyses for predicting performance of culverts generally assume plane strain conditions, the buckling theories reviewed herein are concerned with the two-dimensional problem in which sections transverse to the axis of the pipe are assumed to behave identically.…”
Section: Buckling Theoriesmentioning
confidence: 99%
“…The circumferential strain can also be expressed as By substituting Equations (6) and (7) into Equation From Equations (4) and (10) , tne longitudinal stresses of Equation (11) are…”
mentioning
confidence: 99%
“…Equation (6) can now be minimized for P with respect (9) Since P in (9) is proportional to m 2 , m must be equal to one in all cases when N is greater than 0.…”
mentioning
confidence: 99%